Using Cost-Effectiveness Analysis to Prioritize Spending on Traffic Safety - Ecola, Liisa (RAND Corporation, 2015)
This report examines how traffic safety funding could be spent to reduce motor vehicle crash-related injuries and deaths. Specifically, it assesses three issues: the most cost-effective interventions at the national and state levels, whether to allocate incremental funding increases to all states or spend the funds in targeted states, and how best to allocate funds that target drunk driving.